Determination of Metals in Walnut Oils by Means of an Optimized and Validated ICP-AES Method in Conventional and Organic Farming Type Samples - Natalia Manousi; Natasa P. Kalogiouri; Aristidis Anthemidis; George A. Zachariadis (Separations, 2021)
Agricultural products are indispensable for equilibrated diets since they discharge minerals and several bioactive constituents. Considering the increasing demand for organic products, research has been conducted over recent years to investigate whether organically grown food products are chemically different compared to those produced with conventional farming. In this work, a novel inductively coupled plasma atomic emission spectrometric method was developed and validated for the determination of nutrient and toxic elements in walnut oils produced with conventional and organic farming. The method presented good linearity (r2 > 0.9990) for each element at the selected emission line. The limits of detection and limits of quantification ranged between 0.09 μg g−1 to 2.43 μg g−1 and 0.28 μg g−1 to 8.1 μg g−1, respectively. Method accuracy and was assessed by analyzing the certified reference materials BCR 278-R and spiked walnut oil samples. The determined metals were quantified, and the results were analyzed by Student’s t-test to investigate the differences in the elemental profile of the walnut oils according to type of farming (conventional or organic).